Mechanism for Settlement of Gross Human Rights Violations - Nur Asmarani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study is entitled Mechanism for Settlement of Serious Human Rights Violations, with the aim of knowing and analyzing the mechanism for settlement of serious human rights violations and its obstacles. The legal research method used is the normative legal research method which emphasizes more on literature studies with primary legal materials, secondary legal materials and tertiary legal materials, using qualitative analysis. The results of this study reveal that the settlement of serious human rights violations can be carried out through the court mechanism and the truth and reconciliation commission mechanism. The obstacles in resolving serious human rights violations are more related to the substance. The mechanism for resolving serious human rights violations is not effective because it adopts the principle of retroactive and no expiration. In addition, the substance of determining the implementation of the human rights court is not effective, thus hampering the further examination process.